PENGARUH PEMBERIAN EKSTRAK ETHANOL KULIT JERUK PURUT (Citrus hystrix) TERHADAP PENURUNAN KADAR KOLESTEROL TOTAL PADA MENCIT BALB/C - Lani, Wa Ode Rohya Nuur; Effendy, Devi Savitri; Jufri, Nurnashriana (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Hypercholesterolemia is a condition where cholesterol levels in the blood exceed normal limits. One alternative method that can reduce total cholesterol levels is utilizing herbal plants, such as kaffir lime peel extract. This study aims to examine the relationship between ethanol extract of kaffir lime peel (Citrus hystrix) on reducing total cholesterol levels in BALB/C mice. In laboratory experiments, the study used a non-randomized pre-test and post-test design with a control group. Data analysis was performed using Paired T-Test and One-Way ANOVA methods, as well as Post-Hoc LSD further test. The results showed that the administration of kaffir lime peel ethanol extract at a dose of 70 mg/g BW resulted in total cholesterol levels of 187.5 mg/dL (P1), while a dose of 140 mg/g BW showed levels of 171.7 mg/dL (P2), and the highest dose of 280 mg/g BW resulted in levels of 145.5 mg/dL (P3). These results indicate a significant decrease in cholesterol levels (p < 0.005) of BALB/C mice. In addition, mice fed a high-fat diet experienced a decrease in total cholesterol levels after receiving kaffir lime peel ethanol extract treatment.